In situ electrochemical deposition of a bismuth/cerium dioxide/reduced graphene oxide nanofilm for enhanced Pb2+ sensing performance. (16th August 2022) - Zhao, Nan; Lian, Huiting; Yu, Yaming
Abstract : A Bi/CeO2 /rGO/FTO sensing platform was constructed by in situ electrochemical deposition for sensitive detection of Pb 2+ with a detection limit of 0.00045 μM. Abstract : A novel bismuth/cerium oxide/reduced graphene oxide (Bi/CeO2 /rGO) platform was prepared on an FTO electrode via an in situ electrochemical deposition method, which was employed for the detection of Pb 2+ . The differential pulse anodic stripping voltammetry (DPASV) results demonstrated that the Bi/CeO2 /rGO/FTO sensing platform exhibited good electroanalytical performance. The linear calibration curve for Pb 2+ ranged from 0.001 to 2 μM with a detection limit of 0.00045 μM (S/N = 3). The resulting data were compared with some other reported sensors. The present electrochemical sensor possessed high sensitivity, anti-interference ability, stability and reproducibility for the detection of Pb 2+ . The improved Pb 2+ sensing performance was attributed to the synergetic effect, where rGO was employed as a supporter to improve electron transport and CeO2 was used to increase the stability of rGO and prevent the re-stacking of rGO. Calculations based on density functional theory (DFT) revealed that the Bi/CeO2 /rGO/FTO possessed lower Gibbs free energy for the detection of Pb 2+ in comparison with the rGO/FTO and CeO2 /rGO/FTO, which might further explain the improved sensitivity of the Bi/CeO2 /rGO/FTO electrode. The proposed Bi/CeO2 /rGO/FTO sensing platform was relatively facile, nontoxic and low-cost. Consequently, it was successfully applied for the analysis of Pb 2+ in actual water samples.